Munidopsis geyeri and M. exuta (Crustacea: Munidopsidae): A study of two deep-sea, amphi-Atlantic species that co-occur in the southern Gulf of Mexico - Gaytán-Caballero, Adriana; Escobar-Briones, Elva; Robles, Rafael; Macpherson, Enrique (Zootaxa, 2022)
The history of colonization and dispersal of fauna among deep-sea chemosynthetic ecosystems remains enigmatic and poorly understood. The distribution of squat lobsters of the genus Munidopsis Whiteaves, 1874 can be influenced by the rich organic matter and associated organism communities of chemosynthetic ecosystems. The present work analyzed the molecular relationships and morphology of individuals from different populations of Munidopsis exuta Macpherson & Segonzac, 2005 and M. geyeri Pequegnat & Pequegnat, 1970 in such ecosystems along the Atlantic Equatorial Belt, including the Chapopote Knoll, in the southern Gulf of Mexico. Munidopsis geyeri is re-described based on the present findings and reference to the literature. This analysis documented the genetic distances, as well as range of variation in the diagnostic characters that support the separation of M. exuta and M. geyeri. Our results confirm that the two species coexist in seep ecosystems and have an amphi-Atlantic distribution.